Sedimentary Characteristics, Xrd, Ftir, Uv-Vis And Rock-Eval Pyrolysis of Black Shale Intervals of the Semantan Formation, Peninsular Malaysia - Sajid, Z. (Asian Research Publishing Network, 2020)
This study provides a systematic characterization of Triassic turbidites associated black shale of the Semantan Formation, extensively distributed in the NS part of the Central Belt, Peninsular Malaysia. Sedimentary characteristics, XRD, FTIR, UV-Vis, and Rock-Eval pyrolysis analysis of the black shale from four different localities were studied. XRD analysis shows that illite and kaolinite are dominant clay minerals with abundant traces of non-clay mineral such as quartz. FTIR spectra indicate the presence of aromatic carbon, aromatic C-H in plane bending, and aromatic C-H out of plane bending, OH functional group within black shale organic matter, and traces of quartz. TOC contents are highly variable (0.2-3.67, average: 1.37 wt ) and sourced from allochthonous organic material. The rock-Eval analysis shows that the black shale of the Semantan Formation comprises Type-III kerogens, which propose organic input from terrestrial high plants. UV-Vis absorption ratios E2/E4 (A254/A436) are also used to distinguish between the terrestrial and autochthonous sources of organic matter. Â© 2020. All Rights Reserved.